Transforming Social Movements: Jogja Ora Didol’s Use of Information and Communication Technology - Asmarawati Handoyo; Yuli Isnadi (Profetik: Jurnal Komunikasi, 2024)
ICT as a communication transmission tool has long been a strong factor in shaping political mobilization in many social movements in various social and political events in the world. This research aims to describe the Jogja Ora Didol (JOD) movement in utilizing Information and Communication Technology (ICT). JOD is a movement resisting the bad impact of Yogyakarta’s development policies since 2013. Using the case study and employing secondary data, the investigation was conducted on the JOD’s social media, such as Facebook, Instagram, X (Twitter), and YouTube. We analyzed the utilization of social media in JOD’s movement from some of the features, contents, strategies, messages, and receivers. We also analyzed its impact on offline movement. As a result, we found several findings. First, JOD exploited the features of social media in developing the attractive movement’s strategy. Second, JOD creates a deliberating public space by encouraging anyone to join their movement. Third, the form of participants’ support is according to their capacity and capability. Fourth, JOD used social media to connect online and offline movement agendas. As the impact, fifth, the JOD’s engagement, agenda, and network become strong. In conclusion, we argue that these findings contribute to the current debates between ICT and social movements